Memahami Konsumsi Rumah Tangga yang Berkelanjutan: Analisis Berbasis TPB terhadap Niat Pembelian Produk Ramah Lingkungan di Indonesia - Anggun Wida Prawira; Suryani; Sunusi Dauda; Nissa Aurellia Putri (Journal of Economics, Management, and Accounting, 2025)
This study investigates Indonesian consumers’ intentions to purchase eco-friendly household  This study examines consumer intentions toward eco-friendly household products in Indonesia using the Theory of Planned Behaviour (TPB) as the primary analytical framework. Relying exclusively on qualitative document analysis, the research synthesizes findings from reports, policy documents, and institutional publications to explore how attitudes, subjective norms, and perceived behavioral control shape sustainable purchasing intentions. Results indicate that consumers develop positive attitudes when they perceive eco-friendly products as beneficial for the environment, energy efficient, safe, and cost-effective. Subjective norms, particularly those emerging from family and close social groups, exert strong influence within Indonesia’s collectivist cultural context. Perceived behavioral control is shaped by environmental knowledge, green trust, product availability, affordability, and the clarity of environmental information, which together determine consumers’ sense of capability to adopt sustainable products. Despite rising environmental awareness, barriers such as limited product access and price premiums continue to inhibit intention-to-behavior conversion. The study highlights the importance of expanding TPB with contextual variables such as knowledge and trust to enhance explanatory power. These insights provide implications for policymakers, manufacturers, and sustainability advocates aiming to strengthen eco-friendly household consumption in Indonesia